Crizotinib inhibits hyperpolarization-activated cyclic nucleotide-gated channel 4 activity. Issue 1 (December 2017) - Zhang, Zhushan; Huang, Tai-Qin; Nepliouev, Igor; Zhang, Hengtao; Barnett, Adam; Rosenberg, Paul; Ou, Sai-Hong; Stiber, Jonathan
Abstract Background Sinus bradycardia is frequently observed in patients treated with crizotinib, a receptor tyrosine kinase inhibitor used for the treatment of anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC). We investigated whether crizotinib could influence heart rate (HR) through direct cardiac effects. Methods The direct effect of crizotinib on HR was studied using ECG analysis of Langendorff-perfused mouse hearts. The whole-cell patch clamp technique was used to measure the effects of crizotinib on the hyperpolarization-activated funny current, If, in mouse sinoatrial node cells (SANCs) and hyperpolarization-activated cyclic nucleotide-gated channel 4 (HCN4) activity in HEK-293 cells stably expressing human HCN4. Results Crizotinib resulted in a dose-dependent reduction in HR in isolated intact mouse hearts with a half maximal inhibitory concentration (IC50) of 1.7 ± 0.4 μmol/L. Because ECG analysis revealed that crizotinib (0–5 μmol/L) resulted in significant reductions in HR in isolated mouse hearts without changes in PR, QRS, or QT intervals, we performed whole-cell patch clamp recordings of SANCs which showed that crizotinib inhibited If which regulates cardiac pacemaker activity. Crizotinib resulted in diminished current density of HCN4, the major molecular determinant of If, with an IC50 of 1.4 ± 0.3 μmol/L. Crizotinib also slowed HCN4 activation and shifted the activation curve to the left towards more hyperpolarized potentials. Conclusions Our results suggest that crizotinib's effects on HCN4 channels play a significant role in mediating its observed effects on HR.